National development banks' investments in climate resilient infrastructure: challenges and prospects - Ramathuba, Vivian (Graduate School of Business (GSB), 2026)
This thesis explores the challenges faced by National Development Banks (NDBs) in facilitating investments toward low-carbon and climate-resilient sustainable infrastructure in South Africa. It emphasises their critical role in addressing substantial financing gaps essential for meeting the Nationally Determined Contributions (NDC) commitments under the Paris Agreement. As global priorities increasingly shift toward sustainable development goals, NDBs are undergoing significant transformation, transitioning from their traditional roles as financiers to becoming proactive mobilisers of investment. This pivotal shift is examined in this study within the broader context of a renewed interest in these banks, recognising them as essential policy tools for spearheading rapid and sustainable development initiatives. Through qualitative interviews with 12 experts in climate finance and related fields, the study illustrates how NDBs utilise financial instruments such as concessional loans, blended finance, and long-term financing to mitigate perceived high risks and attract private capital, particularly in sectors prone to high risks like water management and climate-resilient transport. Additionally, NDBs can be mandated by the government to channel substantial international funds into national sustainable infrastructure projects effectively. This mission-oriented approach underscores the unique position of NDBs as critical intermediaries and implementers in the national climate strategy. Despite their potential to bridge vast funding gaps and align their focus with the Paris Agreement, NDBs encounter significant challenges, including policy inadequacies, coordination difficulties, financial constraints, and external economic pressures. This study proposes innovative strategies for NDBs, such as expanding blended finance models, implementing risk mitigation mechanisms, and enhancing institutional capacities to support mobilising funding for sustainable and low-carbon infrastructure. The findings highlight NDBs' ability to adapt to market conditions and regulatory environments, highlighting their pivotal role in transforming South Africa's infrastructure financing landscape to achieve its NDC objectives. Furthermore, this research underscores the importance of strategic policy alignment and innovative financing approaches, including using guarantees and partnerships with international climate funds to enhance project bankability and enable significant private sector participation. Ultimately, this study demonstrates that NDBs are crucial in driving the investment towards a climate-resilient infrastructure in South Africa.